2020
DOI: 10.1016/j.finmar.2019.100511
|View full text |Cite
|
Sign up to set email alerts
|

Social media, financial reporting opacity, and return comovement: Evidence from Seeking Alpha

Abstract: In this study we develop a model to analyse the interplay between social media coverage, financial reporting opacity and stock return co-movement. Our model predicts a negative association between social media coverage and co-movement, because social media coverage lowers the information acquisition and processing cost for investors and therefore facilitates the incorporation of firm-specific information into stock price, which leads to reduced comovement. It is also predicted that such effect is more pronounc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 44 publications
1
19
0
1
Order By: Relevance
“…We examine the news effect on stock markets by using a media coverage index, which we retrieved from RavenPack's website, as a proxy for the news effect during the COVID-19 period. This is in line with previous studies that have also used media coverage as an important proxy for news effect (Rogone et al, 2020;Haroon and Rizvi, 2020a;Subrhamanyam, 2019;Ding et al, 2019;Narayan, 2019Narayan, , 2020a. We further estimate bivariate time-series regressions for each of the stock price indices using the ordinary least squares (OLS) technique.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…We examine the news effect on stock markets by using a media coverage index, which we retrieved from RavenPack's website, as a proxy for the news effect during the COVID-19 period. This is in line with previous studies that have also used media coverage as an important proxy for news effect (Rogone et al, 2020;Haroon and Rizvi, 2020a;Subrhamanyam, 2019;Ding et al, 2019;Narayan, 2019Narayan, , 2020a. We further estimate bivariate time-series regressions for each of the stock price indices using the ordinary least squares (OLS) technique.…”
supporting
confidence: 53%
“…This index is the percentage of all news sources that cover coronavirus related information. Recent studies (Rogone et al, 2020;Haroon and Rizvi, 2020a;Subrhamanyam, 2019;Ding et al 2019) used MCI to proxy for coronavirus news effect as well. The CPI index measures the percentage of news chatter that refers to panic or hysteria related to the virus.…”
Section: Data and Methodology A Datamentioning
confidence: 99%
“…),Ding et al (2019) andRogone et al (2020), we use the Ravenpack finance for Panic Index, Global Sentiment Index and Media Coverage. Ravenpack aggregates news from hundreds of different news sources and creates daily index of level of hysteria inducing news (Panic), general sentiment of the news for the day based on an artificial intelligence index (Sentiment) and the quantity of coronavirus news as compared to other news (Media Coverage).…”
mentioning
confidence: 99%
“…As an important channel for transmitting information, social media improves the financial market information environment. A large number of studies have shown that the use of social media by companies reduces information asymmetry among investors (Blankespoor et al, 2014;Prokofieva, 2015;Li et al, 2018;Ding et al, 2020), allows them to obtain timely market feedback (Uyar and Boyar, 2015), eases the market's negative reaction to a product crisis (Lee et al, 2015) and predicts future earnings and company value (Chen et al, 2014;Bartov et al, 2018;Tang, 2018;Green et al, 2019;Chung et al, 2020;Huang et al, 2020).…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%